A Pilot Examination of Differences in College Adjustment Stressors and Depression and Anxiety Symptoms Between White, Hispanic and White, Non-Hispanic Female College Students. (July 2016) - Holliday, Ryan; Anderson, Elizabeth; Williams, Rush; Bird, Jessica; Matlock, Alyse; Ali, Sania; Edmondson, Christine; Morris, E. Ellen; Mullen, Kacy; Surís, Alina
Differences in four adjustment stressors (family, interpersonal, career, and academic), and depression and anxiety symptoms were examined between White, non-Hispanic and White, Hispanic undergraduate college female students. White, Hispanic female college students reported significantly greater academic and family adjustment stressors than White, non-Hispanic students. None of the socioeconomic or demographic variables predicted adjustment stress, depression, or anxiety. Findings are discussed in terms of college mental health outreach and future research directions.